HISTORICAL RESONANCES OF AFRO-BRAZILIAN RELIGIONS IN SANTA CATARINA STATE: FLORIANÓPOLIS, ITAJAÍ AND JOINVILLE (Orfeu, 2020)
This is a study on the historical process of Afro-Brazilian religions in Santa Catarina State, especially Umbanda and Candomblé in the region between Florianópolis and Joinville. In order to understand why these religions are so closely related, a historical investigation was carried out, supported by the lens of Ethnomusicology (BLACKING, 2000), Anthropology (LAPLANTINE, 2012), and Cultural Studies (GARCÍA CANCLINI, 2015). Given the scarcity of research on this topic in the region, historical resonances were adopted as a strategy. Local bibliographies of History, Anthropology, Ethnomusicology, Humanities and Afro-religiosity were used. There are also oral reports and intense field experience. Due to geographical, political and economic factors, the history of Candomblé in Santa Catarina goes through Umbanda, Kardecismo, healers and the figure of the indigenous caboclo; with bonds in Rio de Janeiro and Bahia. Faced with cultural metamorphoses, the Afro-Brazilian religions of Santa Catarina are characterized by religious freedom and doctrinal hybridism.
Keywords: Afro-Brazilian Religions; Candomblé; Umbanda; Doctrinal hybridism